The Influence Of Pricing Strategy And Product Strategy On Coffee Purchasing Decisions At Padang Pagun Lahat Home Coffee Business - Oka Mahendra; Rudi Eduar; Hestin Hestin (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine how pricing strategy and product strategy partially and simultaneously influence coffee purchasing decisions at the Rumah Padang Pagun Coffee Shop in Lahat. The sample size for this study was 60 respondents. The sampling method used was incidental sampling. The results showed a significant effect between pricing strategy and coffee purchasing decisions at the Rumah Padang Pagun Coffee Shop in Lahat. There was also a significant effect between product strategy and the competitiveness of coffee products at the Kiro Coffee Shop in Lahat. The F-test showed that pricing strategy and product strategy simultaneously influenced coffee purchasing decisions at the Rumah Padang Pagun Coffee Shop in Lahat.